2020
DOI: 10.4236/ajps.2020.111002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cytological Effects of Food Preservative Potassium Metabisulphite to <i>Allium cepa</i>

Abstract: With the unprecedented development of the food industry, food preservatives have gained a leading role in food processing. In this study, investigations were carried out to assess the cytological effects of potassium metabisulphite (PMB) to onion (Allium cepa), one of the most used plants for determining the cytotoxic and genotoxic effects of different chemicals. Meristematic roots of A. cepa were treated with PMB solutions in different concentrations, ranging from 10 mg/l to 35 mg/l for 6, 12 and 24 h alongsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Previous reports suggested that reduction in MI values may be the result of the discontinuation of the replication of DNA or blockage during the G 2 phase of the cell cycle or disturbances in the mitotic phases such as insufficient synthesis of ATP during spindle fiber formation and elongation, Which can prevent the cells from further division (Sudhakar et al 2001, Sreeranjini andSiril 2011, Pandey et al 2014). The appearance of various cytological and chromosomal aberrations in root apical meristem cells of A. cepa after treatment with different chemicals attributed to their cyto-genotoxic effect (Rosculete et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports suggested that reduction in MI values may be the result of the discontinuation of the replication of DNA or blockage during the G 2 phase of the cell cycle or disturbances in the mitotic phases such as insufficient synthesis of ATP during spindle fiber formation and elongation, Which can prevent the cells from further division (Sudhakar et al 2001, Sreeranjini andSiril 2011, Pandey et al 2014). The appearance of various cytological and chromosomal aberrations in root apical meristem cells of A. cepa after treatment with different chemicals attributed to their cyto-genotoxic effect (Rosculete et al 2019).…”
Section: Resultsmentioning
confidence: 99%